Biogeochemistry of Household Dust Samples Collected from Private Homes of a Portuguese Industrial City - Amélia P. Marinho-Reis; Cristiana Costa; Fernando Rocha; Mark Cave; Joanna Wragg; Teresa Valente; Amália Sequeira-Braga; Yves Noack (Geosciences, 2020)
The main objectives of the present study were to (i) investigate the effects of mineralogy and solid-phase distribution on element bioaccessibility and (ii) perform a risk assessment to calculate the risks to human health via the ingestion pathway. Multiple discriminant analysis showed that the dust chemistry discriminates between indoor and outdoor samples. The solid-phase distribution of the elements in indoor dust indicated that a large proportion of zinc, nickel, lead, copper, and cobalt is associated with an aluminum oxy-hydroxides component, formed by the weathering of aluminum silicates. This component, which seems to influence the mobility of many trace elements, was identified for a group of indoor dust samples that probably had a considerable contribution from outdoor dust. An iron oxide component consisted of the highest percentage of chromium, arsenic, antimony, and tin, indicating low mobility for these elements. The bioaccessible fraction in the stomach phase from the unified BARGE method was generally high in zinc, cadmium, and lead and low in nickel, cobalt, copper, chromium, and antimony. Unlike other potentially toxic elements, copper and nickel associated with aluminum oxy-hydroxides and calcium carbonates were not extracted by the stomach solutions. These trace elements possibly form stable complexes with gastric fluid constituents such as pepsin and amino acid. Lead had a hazard quotient >1, which indicates the risk of non-carcinogenic health effects, especially for children.